The Representation Methods of Addiction in Iran's Movies - M Soltani Gerd Faramarzi; AA Esmaeil Zadeh (Drug Control Headquarters, Research and Education Office, 2014)
Objectives: The aim of research was answer to this question that movie after revolution how was represented matters of addicts and addiction? Method: For answering to question 33 movies made between 1360 till 1390 which main characters were addicts, studied by content analysis. Results: The results showed that in studied movies, addicts were men, bachelor, or divorced and majority of them were educated. Also, Heroin consumption was more that other narcotics in movies. Addicts' personal home and his/her friends' home were important places for consumption and friends were important narcotics preparators and they most important factor in initiate of consumption. On the other hand, divorce and child selling had the most frequency in movie. Family and friend groups were the most important factors in addiction and its etiology. Conclusion: The results showed that movies represented one kind of popular addiction study that overlapped with academic addiction study.